Soil moisture and soybean physiology affected by drought in an integrated crop‑livestock system - Martins, Amanda Posselt; de Andrade Costa, Sérgio Ely Valadão Gigante; Anghinoni, Ibanor; Kunrath, Taise Robinson; Cecagno, Diego; Reichert, José Miguel; Balerini, Fabrício; Dillenburg, Lúcia Rebello; Carvalho, Paulo César de Faccio (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the impact of grazing intensities after 11 years of an integrated crop‑livestock system, under no‑tillage, on soil moisture and soybean physiological parameters during a summer season affected by drought. The experiment was established in 2001 on a Rhodic Hapludox. Treatments consisted in the succession of soybean (summer) and a mixed pasture of black oat + Italian ryegrass (winter), under different beef‑cattle grazing intensities: intensive grazing, with 0.10‑m pasture height; moderate grazing, with 0.20‑m pasture height; and no grazing. During the soybean cycle, in the 2011/2012 crop season, rainfall was 40% of the climatological normal. The soil moisture was within the limits of available water both under moderate grazing and no grazing, at 0.00–0.50‑m soil depth, but, under intensive grazing, it was below the permanent wilting point, especially up to the grazing height of 0.20 m. Intensive grazing affected negatively the plant physiology parameters, reaching peaks of ‑2.5 MPa and +6°C for leaf water potential and leaf‑air temperature difference, respectively. Moderate grazing or the absence of grazing, during the winter season, results in similar physiological responses, contributing to soybean plant homeostasis.